EFFICIENCY OF TWO DESIGNS OF TRAWLS IN HIRAKUD RESERVOIR - GEORGE, V C; DAWSON, PERCY; KHAN, A A; VARGHESE, M D; IYER, H KRISHNA (Fishery Technology, 2017)
High opening trawl was found to be effective for the exploitation of bottom and offbottom fishes from Hirakud Reservoir compared to bulged belly trawl.